13 seconds : a look back at the Kent State shootings - Caputo, Philip (New York : Chamberlain Bros., 2005)
Recounts the events surrounding the May 4th, 1970 shooting and the investigations that followed, discussing the impact the event has had on the families and friends of the killed and injured students and on the university.
Keywords: Kent State Shootings, Kent, Ohio, 1970